Estudo da interação de prótons com alvos não homogêneos, aplicados a tomografia com feixes de prótons - Roder, Ana Flávia Vidotti [UNESP] (2014)
Cancer treatment by irradiation with protons has been widely developed so that each decade the number of centers based on this technology increases progressively. However, the planning of routine therapy is performed with images of X- rays, which can cause uncertainties as to the precise positioning of the proton beam on the tumor due to the difference in behavior when interacting with matter. Therefore, it is necessary studying the improvement of computed tomography with protons, whose main function, determine the position of the Bragg peak efficiently. Nevertheless, to develop this technique it is necessary to determine the exact path that the particle travels through the patient's body, which is possible with simulations based on Monte Carlo method. There are several programs that use Monte Carlo for different types of purposes, among which are meant for the transport of the proton: GEANT, FLUKA and MCNPX. The third one was used in this work to evaluate the disturbance in the incident beam of protons in a heterogeneous medium composed of water and equipment simulator compact bone (beam direction perpendicular to the interface) and water-PMMA (beam parallel to the interface). The output energy, position and angle of the protons were studied considering only primary particles and for all particles